SSH-BM-I, a Tryptamine Derivative, Stimulates Mineralization in Terminal Osteoblast Differentiation but Inhibits Osteogenesis of Pre-committed Progenitor Cells - Yoshikazu Mikami; Masanori Somei; Hiromasa Tsuda (Elsevier, 2011)
Abstract.: SSH-BM-I was synthesized from tryptamine by using a newly developed synthetic method, and it has structural similarity to bromomelatonin. Recently, it had been reported that SSH-BM-I increases osteoblasts in scales of gold fish. However, the effect of SSH-BM-I on osteoblast differentiation in mammalian cells has not yet been examined. Therefore, this study examined the effect of SSH-BM-I on osteoblast differentiation in mesenchymal progenitor-like cells and mature osteoblast-like cells. SSH-BM-I enhanced terminal osteoblast differentiation, as indicated by mineralization, which was accompanied by upregulation of the osteogenic marker genes bone sialoprotein (BSP) and osteocalcin (OC). However, in mesenchymal progenitor ROB-C26 cultures, no mineralized nodules were observed regardless of SSH-BM-I treatment, although BMP-2 was able to induce nodule formation in these cells. Furthermore, BMP-2-induced nodule formation was suppressed by SSH-BM-I treatment in ROB-C26 cultures. We further investigated the impact of the timing and duration of SSH-BM-I treatment on osteoblast differentiation. The effect of SSH-BM-I treatment on osteoblast differentiation of ROB-C26 in the presence of BMP-2 switches from negative to positive sometime between day 6 and 9, because SSH-BM-I treatment enhanced the formation of mineralized nodules when it was started on day 9, but suppressed nodule formation when it was started at day 6 or earlier. These results suggest that the stimulatory effects of SSH-BM-I on the formation of mineralized nodules depend on the degree of cell differentiation. Keywords:: SSH-BM-I, tryptamine, osteoblast, mineralization